Bridging Cognitive Gaps in Physics Education: The Role of Age, Motivation, and Instructional Strategies - Adeniyi Michael Adeduyigbe; Uchenna Kingsley Okeke; Sam Ramaila (Journal of Research in Environmental and Science Education, 2026)
This paper explores the intersection of age, motivation, and instructional strategies in shaping students’ understanding of physics concepts. A growing body of research suggests that effective physics education must account for the developmental differences among learners, particularly as they move through various cognitive stages. Drawing from Piaget’s theory of cognitive development, the paper emphasizes that while students typically transition from concrete to formal operational thinking during secondary school, this progression is not uniform and is influenced by several factors beyond age, including instructional methods and individual motivation. Some students may reach formal operational thinking earlier and show readiness for abstract reasoning, while others may require additional support and scaffolding. This variability presents a significant challenge for educators aiming to deliver content that resonates with all learners. Younger students often rely on tangible, hands-on experiences to understand physics, whereas older students gradually develop abstract reasoning skills necessary for engaging with more complex scientific principles. Motivation, both intrinsic and extrinsic, plays a critical role in student engagement and persistence, with high self-efficacy and interest in physics contributing significantly to conceptual mastery. The paper advocates for age-responsive instructional strategies that are tailored to students’ developmental readiness, including scaffolding, differentiated instruction, inquiry-based learning, and the use of technology to personalize and enrich the learning experience. Based on these insights, the paper presents practical recommendations for curriculum development and teaching, such as incorporating real-world applications, integrating cross-disciplinary content, promoting equity and inclusion, and enhancing teacher professional development. By aligning instructional practices with students’ cognitive stages and motivational drivers, educators can bridge learning gaps, foster deeper conceptual understanding, and create more inclusive and effective physics classrooms that support long-term academic success.